Boarded patients, blurred benchmarks: an opportunity for CMS - Elyssa F L Grogan; Natalia Sifnugel; Arjun K Venkatesh; Ula Y Hwang (Health Affairs Scholar, 2026)
Abstract The Centers for Medicare and Medicaid Services recently introduced two clinical quality measures that intend in part to disincentivize hospital boarding: a patient safety concern that involves holding admitted patients in the emergency department while an inpatient bed is unavailable. The Age-Friendly Hospital Measure, a structural measure, asks hospitals to attest to having protocols in place to reduce boarding for older patients. The Emergency Care Access and Timeliness Measure, an intermediate outcome measure, will require hospitals to report on the proportion of boarded patients. Each measure was developed under a different parent quality reporting program—one inpatient and one outpatient—which has the unintended consequence of producing meaningful variation between the measures. We describe opportunities to standardize and synergize the Age-Friendly Hospital Measure and Emergency Care Access and Timeliness Measure to capture the prevalence of boarding uniformly, prevent gamesmanship, and enhance their impact on hospital performance. Particularly, we highlight the importance of stratifying ECAT by the older adult patient population to complement AFHM and since older adults are uniquely vulnerable to boarding and its associated safety risks.